A course in miracles made easy : mastering the journey from fear to love - Cohen, Alan, 1950- (Hay House, Inc., 2015)
"A Course in Miracles (ACIM)--the self-study spiritual-thought system that teaches the way to love and forgiveness--has captured the minds and hearts of millions of people, and delivered inner peace where fear and pain once prevailed. Its universal message is unsurpassed in its power to heal. Yet many students report that they have difficulty grasping the principles, or encounter resistance to the lessons. So, even while they yearn for the spiritual freedom the Course offers, they put the book aside, hoping one day to get to it. Alan Cohen, ACIM student and teacher for over 30 years, takes the Big Picture ideas of the Course and brings them down to earth in practical, easy-to-understand lessons with plenty of real-life examples and applications. A Course in Miracles Made Easy is the Rosetta stone that will render the Course understandable and relatable; and, most importantly, generate practical, healing results in the lives of students. This unique reader-friendly guide will serve longtime students of the Course, as well as those seeking to acquaint themselves with the program"--